1993
DOI: 10.1099/00221287-139-4-753
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting competence in a high frequency of transformation marine Vibrio

Abstract: Natural plasmid transformation may be a mechanism for the horizontal transfer of non-conjugative plasmids in the marine environment, yet there are few marine model systems available for the study of this process. Using multimers of IncQ/P4 plasmids and a filter transformation assay, we have measured the effects of nutrients, salinity, temperature, as well as the development and maintenance of competence for genetic transformation in the high frequency of transformation (HFT) marine Vibrio strain WJT-1C. Transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…pQSR50 is a derivative of Rl162 [24] which contains transposon Tn5 and encodes resistance to the antibiotics kanamycin and streptomycin [25]. pQSR50 was used in earlier transformation studies [20][21][22][23]. Plasmid DNA was purified and multimerized as previously described [20].…”
Section: Transforming Dna and Gene Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…pQSR50 is a derivative of Rl162 [24] which contains transposon Tn5 and encodes resistance to the antibiotics kanamycin and streptomycin [25]. pQSR50 was used in earlier transformation studies [20][21][22][23]. Plasmid DNA was purified and multimerized as previously described [20].…”
Section: Transforming Dna and Gene Probesmentioning
confidence: 99%
“…Recently we have developed a marine model system for the investigation of natural plasmid transformation in the environment [20,21]. Using this system we have demonstrated the potential for natural transformation in the marine environment [22] and the potential for inter-and intraspecific plasmid transfer to occur between marine Vibrio strains or between E. coli and Vibrio strains [23].…”
Section: Introductionmentioning
confidence: 99%
“…After incubation, cells were lysed by placing membranes, colony side up, on Whatman 3MM filter paper soaked with 2 x SSC, 5 YO (w/v) SDS for 2 min, followed by heating at maximum power in a 650 W microwave oven for 2.5 min, as described by Buluwela e t al. (1989) and Frischer et al (1990). The membranes were transferred to filter paper soaked with denaturing solution (0.5 M NaOH, 1-5 M NaCl) and incubated for a further 7 min.…”
Section: Methodsmentioning
confidence: 99%
“…Addition of low nutrient levels (100 mg l-1 of peptone plus 20 mg 1-1 of yeast extract) to any of the water column microcosms, resulted in increased transformation frequencies, whereas the addition of 10-times higher nutrient levels appeared to depress transformation frequencies. In a further study, it was found that non-growing WJT-1C cells were able to maintain competence for at least 10 days when held either in spent rich medium or artificial seawater with no added nutrients [19]. Also, WJT-1C showed no significant difference in transformation frequency by plasmid pQSR50 when the cells were grown in artificial seawater containing yeast extract and peptone concentrations ranging from 10 to 2000 and 50 to 10000 mg 1 -a, respectively, in contrast to results from earlier studies [18].…”
Section: Transformationmentioning
confidence: 93%